Increasing Crop Diversity and Productivity of Rice (Oryza Sativa L.)-Wheat (Triticumaestivum L.) Cropping System through Bed Planting (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this paper have changed from 35-44 to 37-46.Adoptions of new crop establishment methods, changing management practices and inclusion of new crops in the rice-wheat cropping system are very important for maintaining and increasing system productivity. Experiments were conducted at the Bangladesh Rice Research Institute, Gazipur and farmers fields in Chuadanga during 2002-03 to evaluate the performances of rice, wheat and mungbean in bed planting and to evaluate the system productivity of Rice-Wheat-Mungbean cropping pattern. Wheat-Mungbean-Direct seeded rice (DSR), Wheat-Mungbean-Transplant rice (TPR), Wheat-Fallow-DSR and Wheat-Fallow-TPR cropping system under bed planting and conventional methods were evaluated. Grain yields of wheat, mungbean, rice and rice equivalent yield (REY) under bed planting were significantly higher (25.41, 40.91, 13.00 and 21.12%, respectively) than the conventional method. The Wheat-Mungbean-Rice cropping pattern produced significantly greater REY (38.25%) than Wheat-Fallow-Rice cropping pattern. Total variable cost was lower (17.33%) in bed planting than conventional method. Gross return, gross margin and benefit-cost ratio of Wheat-Mungbean-Rice cropping system in bed planting were higher (14.43, 40.99 and 38.52%, respectively) than the conventional method.Bangladesh Rice j. 2015, 19(2): 37-46